Chemical profiling and quantification analysis of flavonoids in different varieties of Euryales Semen by ultra‐high‐performance liquid chromatography with tandem mass spectrometry. Issue 7 (10th February 2023) - Li, Dishuai; Cheng, Xuemei; Jiang, Zheng; Shi, Zunrui; Qu, Cheng; Yan, Hui; Wu, Qinan
Abstract : Euryales Semen was a traditional Chinese medicine, which has been commonly used to treat spermatorrhea, enuresis, and frequent urination. Flavonoids were a critical ingredient in determining the function and quality of Euryales Semen. At present, no effective method has been established for the qualitative of Euryales Semen flavonoids. In this study, an ultra‐high‐performance liquid chromatography‐quadrupole‐time of flight‐mass spectrometry method was established for flavonoids. By comparison with standard or literature data, 32 flavonoid compounds have been identified in Euryales Semen. Based on the qualitative results, an ultra‐high‐performance liquid chromatography‐triple quadrupole tandem mass spectroscopy method was developed for the main components, and the linearity, the limit of detection, limit of quantification, repeatability, precision, stability, and recovery of the method were verified. The principal component analysis and the hierarchical clustering heatmaps analysis showed that the 30 batches of samples were distinctly separated into the North Gordon Euryale and South Gordon Euryale, and the measured contents of the six flavonoids in North Gordon Euryale were more abundant than in South Gordon Euryale, especially isoquercitrin, hesperetin, and quercetin. It provided a scientific basis for the quality control of Euryales Semen and a theoretical basis for the rational utilization of Euryales Semen resources.